2020
DOI: 10.21203/rs.3.rs-19845/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A patients’ view of OA: the Global Osteoarthritis Patient Perception Survey (GOAPPS), a pilot study

Abstract: Background: Globally, osteoarthritis (OA) is the third condition associated with disability. There is still poor treatment in OA but science holds the key to finding better treatments and a cure. It is essential to learn what’s important to patients from them to implement the most effective OA management. The OA Patients Task Force, conducted the Global OA Patient Perception Survey (GOAPPS)-the first global survey made by patients to analize the quality of life (QoL) & patient perceptions of care across co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Nevertheless, oral medications, and in particular nonsteroidal anti‐inflammatory drugs, have potential and well‐documented side‐effects, such as gastrointestinal toxicity, cardiovascular adverse effects and nephrotoxicity, 39 whereas exercise has been shown to have benefits that go beyond joint health, reducing the risk of developing a wide array of comorbidities and promoting a healthy lifestyle 40 . Moreover, evidence showed that individuals with OA are seeking non‐pharmacological and non‐surgical treatments for their conditions, and they want more information about these treatments, which highlights the likelihood that they might be open to undergoing exercise and physiotherapy interventions if educated on their benefits 41,42 . This was also retrieved in our interviews in which patients understood the importance of being active and saw exercise as a concrete support to their care, something that one can see while doing it, in contrast to medications and supplements that do not immediately show tangible effects.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, oral medications, and in particular nonsteroidal anti‐inflammatory drugs, have potential and well‐documented side‐effects, such as gastrointestinal toxicity, cardiovascular adverse effects and nephrotoxicity, 39 whereas exercise has been shown to have benefits that go beyond joint health, reducing the risk of developing a wide array of comorbidities and promoting a healthy lifestyle 40 . Moreover, evidence showed that individuals with OA are seeking non‐pharmacological and non‐surgical treatments for their conditions, and they want more information about these treatments, which highlights the likelihood that they might be open to undergoing exercise and physiotherapy interventions if educated on their benefits 41,42 . This was also retrieved in our interviews in which patients understood the importance of being active and saw exercise as a concrete support to their care, something that one can see while doing it, in contrast to medications and supplements that do not immediately show tangible effects.…”
Section: Discussionmentioning
confidence: 99%
“…10 QoL is defined as an individual's perception of their position in life in the context of the culture and value systems in which they live and in relation to their goals, expectations, standards and concerns. 11 OA has a significant impact on patients' daily activities 12 and it is reported that people with hand OA have a clinically relevant lower physical health-related QoL 13 and significant impact on hand function. 14 Previous studies have evaluated the QoL in patients with OA in different joints 11,13 and how hand OA affects their hand functions.…”
mentioning
confidence: 99%